THE USE OF PARTICIPATION POINT SYSTEM IN TEACHING THE ENGLISH SPEAKING SKILL AT THE VII GRADE OF SMPN 4 BARAKA ENREKANG REGENCY - Amelia, Amelia; Dalle, Muhammad Basri; Setiadi, Muhammad Astrianto (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2018)
This research was aimed at finding out the improvement of students’ pronunciation and self-confidence through Participation Point System (PPS) Method in teaching speaking skill. The research method used was class action research design consisting of 4 stages, namely planning, action observation and reflection. It had 2 cycles. The research was implemented on the seventh grade students of SMP Negeri 4Baraka 2016/2017. The researcher took 20 students as the subject of the research. The researcher taught speaking English using PPS Method. The data were gathered after scoring the students’ speaking skill on both pronunciation and self-confidence through diagnostic test and test of cycle I and II. The research findings showed that the mean score of the students’ speaking diagnostic test was 5.22 as categorized poor (low ability) while the mean score of the students’ speaking test in cycle I was 5.34. It had a significant progress but the result still did not reach the determined standard score 7, so the research was proceeded to the cycle II that the researcher gained the mean score 7.00 as categorized good. It showed that the latest progress in the cycle II had reached beyond the determined standard score and there was a significant improvement on the seventh grade students’ speaking skill on both pronunciation and self-confidence in the English teaching using Participation Point System Method at SMP Negeri 4 Baraka 2016/2017.